IMPLIKASI LANDASAN PSIKOLOGI DALAM PENGEMBANGAN KURIKULUM TERHADAP PROSES PEMBELAJARAN PAI DI SEKOLAH DASAR - Abdurrahman Abdurrahman (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2023)
The psychological foundation is the basis of understanding in studying something from the point of view of human characteristics and behavior, especially students. Each student has their own characteristics at each stage of development. Teachers must understand the differences in student characteristics, making it easier for them to organize everything related to the process of delivering learning materials to be more effective. This study aims to analyze the impact of the psychological foundation in curriculum development on the PAI learning process. This research uses a qualitative approach with a type of library research. The data sources in this article come from books and journal articles related to the title of the article. The results showed that implications of the psychological foundation in curriculum development for the learning process of PAI in elementary school are found in three domains, namely the realm of subject matter, learning methods, and learning evaluation. The material taught to elementary-age learners is in the form of definitions and the most in-depth about various kinds. PAI teachers are expected to design learning that allows children to move and change places, apply serious but relaxed methods, and apply learning that makes students work together. Assessment of PAI learning outcomes can be divided into three aspects, namely cognitive, affective, and psychomotor aspects.